Pengembangan Sikap Moderasi Beragama Mahasiswa melalui Mata Kuliah Praktik Ibadah Kemasyarakatan di UIN Fatmawati Sukarno Bengkulu - Mirna Guswenti; Sabarudin Sabarudin; Adi Saputra; Fatimah Nurlatifah (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
Religious moderation is a moderate attitude of understanding and practicing worship in a balanced and not excessive religion. This study aims to describe the implementation of community worship practices and attitude of religious moderation for students of UIN Fatmawati Bengkulu. The research method used descriptive qualitative with determined the research subjects using a purposive sampling technique: students and educators. Data was collected through in-depth interviews and observations. The data validity test in this study is the triangulation of data sources. The study results showed two findings. First, the implementation of community worship practices takes place by focusing on oneself and the surrounding environment, understanding the theory, then practicing lectures slowly, and inviting the community to achieve a strong community of religious understanding and practice. Second, the attitude of religious moderation takes place by internalizing religious values ​​that are neither extreme right nor extreme left, which are carried out in the subject of community worship practices, namely equivalence and fairness.